Impact of pre-admission treatment with non-vitamin K oral anticoagulants on stroke severity in patients with acute ischemic stroke - Hoyer, Carolin; Filipov, Alexandra; Neumaier-Probst, Eva; Szabo, Kristina; Ebert, Anne; Alonso, Angelika (Journal of thrombosis and thrombolysis, 2018)
Non-vitamin K antagonist oral anticoagulants (NOACs) have gained increasing importance for stroke prevention in patients with non-valvular atrial fibrillation (AF). With changing prescription practice, among other factors, clinicians can expect to see rising numbers of patients with ischemic stroke and pre-existing NOAC therapy. Few data exist regarding a potential impact of NOAC on stroke severity and outcome.
Gesehen am 07.09.2020